Immune checkpoint blockade combined with abnobaViscum therapy is linked to improved survival in advanced or metastatic non-small-cell lung cancer patients: a registry study in accordance with the ESMO guidance for reporting real-world evidence - Schad, Friedemann; Thronicke, Anja; Hofheinz, Ralf-Dieter; Klein, Reinhild; Grabowski, Patricia; Oei, Shiao Li; Wüstefeld, Hannah; Grah, Christian (Pharmaceuticals, 2024)
Background: Recent advancements in cancer treatment have shown the potential of immune checkpoint blockade (ICB) plus Viscum album L. therapy in improving survival rates for patients with advanced or metastatic non-small-cell lung cancer (NSCLC). The objective of this study was to investigate factors associated with improved survival in NSCLC patients treated with a combination of ICB and abnobaViscum®. Methods: Patients with advanced or metastatic NSCLC from the accredited Network Oncology registry were included in this real-world data study adhering to ESMO-GROW criteria with ethics approval. Survival outcomes were compared between patients receiving ICB therapy alone versus those receiving combinational ICB plus abnobaViscum® therapy using Kaplan-Meier and multivariable Cox proportional hazard analysis. Results: Among 300 patients (median age 68 years; male/female ratio 1.19), 222 received ICB alone (CTRL group) and 78 received combinational therapy (COMB group). Overall survival was significantly prolonged in the COMB group by 7 months compared to CTRL (13.8 months vs. 6.8 months, p = 0.005) with a survival rate of 16.5% in the COMB group vs. 8.0% in the CTRL group. In programmed death-ligand 1 positive (≥1%) patients treated with first-line ICB, the addition of abnobaViscum® reduced the adjusted hazard of death by 75% (aHR: 0.25; 95%CI: 0.11-0.60, p = 0.02). Conclusions: The addition of abnobaViscum® to ICB is significantly associated with improved survival in patients with advanced or metastatic NSCLC patients, irrespective of age, stage, Eastern cooperative oncology group status, surgery, or radiation. Potential mechanisms include immune modulation, reduced primary ICB resistance, and tumor microenvironment modifications. The findings warrant further validation in randomized controlled trials or registry-based randomized controlled trials. Trial registration: The study was registered (DRKS00013335).